Loneliness and Social Networks in Europe : ISSP Data from 13 European Countries = Usamljenost i društvene mreže u Europi : rezultati ISSP istraživanja za 13 europskih država - Tonković, Željka (Array, 2021)
The paper analyses social causes of loneliness in Europe using cross-national data from the 2017 International Social Survey Programme (ISSP) module "Social Networks and Social Resources" from 13 countries categorised as Northern Europe, Continental Europe, and Central and Eastern Europe. The paper aims to examine loneliness with regard to three specific groups of predictors, related to network, sociocultural and sociostructural aspects. The results suggest that sociability patterns and personal networks are the most important predictors of loneliness. While the frequency of contacts with family members and close friends and the overall number of contacts showed significance, loneliness was primarily related to the quality of personal relationships. Considering sociocultural factors, the obtained findings showed that social trust is consistently associated with lower levels of loneliness. Furthermore, people from Continental Europe were, in general, less lonely than North and East Europeans. Age was an important factor here as respondents from younger age groups were lonelier in Nordic countries than in the other two blocs of countries, while older respondents were lonelier in Central and East European countries. Finally, sociostructural indicators in general showed less predictive value compared to sociability patterns and sociocultural variables. However, when it came to socioeconomic exclusion, this aspect showed a stronger connection with loneliness for the individuals from the Nordic group of countries. The findings of this paper contribute to the vibrant field of contemporary scholarship on loneliness with a fresh perspective based on comparing three large blocs of European countries and an integrated approach to various predictors of loneliness.